2018
DOI: 10.1002/hed.25189
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic stratification of patients with nasopharyngeal carcinoma based on tumor immune microenvironment

Abstract: Our results suggest that PD-L1 expression on tumor cells in combination with CD8-positive TIL density could be a useful predictive biomarker for risk stratification in patients with NPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 45 publications
(103 reference statements)
3
53
0
Order By: Relevance
“…Our data show a positive expression of PD-L1 in 70% of cases, which is consistent with previous reports [12,17,18]. The correlation between PD-L1 expression and better prognosis is consistent with Zhu et al [14] and Lee et al [18] who found PD-L1 to correlate with favorable prognosis in NPC.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our data show a positive expression of PD-L1 in 70% of cases, which is consistent with previous reports [12,17,18]. The correlation between PD-L1 expression and better prognosis is consistent with Zhu et al [14] and Lee et al [18] who found PD-L1 to correlate with favorable prognosis in NPC.…”
Section: Discussionsupporting
confidence: 93%
“…The correlation between PD-L1 expression and better prognosis is consistent with Zhu et al [14] and Lee et al [18] who found PD-L1 to correlate with favorable prognosis in NPC. Interestingly, when CD3+ TIL was combined with PD-L1 expression status as done previously for CD8+ TIL and PD-L1 by Ono et al [12], there was a correlation between patients having combination of low CD3 + TIL and lack tumoral PD-L1 (type II) with shorter OS. It is becoming increasingly evident that antitumor immune response plays a major role in the eradication and/or control of many types of cancer, including head and neck tumors.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The tumor microenvironment (TME) is composed of cellular components such as infiltrating leucocytes, stromal cells and cancer cells, and non-cellular components such as extracellular matrix and various types of soluble biological factors or mediators. Recent studies have implicated the important role of TME, particularly, the function of stromal cells, in NPC pathogenesis and progression [4][5][6][7]. However, the potential mechanisms by which mesenchymal stromal cells (MSC) in TME contribute…”
Section: Introductionmentioning
confidence: 99%